Postpartum Uterine Artery Doppler Indices when Leaving the Placenta In Situ for Placenta Accreta Spectrum - Kassir, Elias; Hernandez-Andrade, Edgar A.; Sibai, Baha M.; Papanna, Ramesha; Soto-Torres, Eleazar E.; Coselli, Jennie O.; Mehl, Sarah T.; Gerulewicz-Vannini, Donatella; Zamorano, Abigail S.; Blackwell, Sean C.; Amro, Farah H. (American Journal of Perinatology, 2025)
This study aimed to evaluate longitudinal changes in uterine artery (UtA) Doppler velocimetry in patients with placenta accreta spectrum (PAS) managed by leaving the placenta in situ (LPIS) postpartum.This is a prospective cohort study of patients with PAS managed by LPIS for either planned interval hysterectomy or uterine preservation who underwent serial postpartum ultrasounds. We included patients who had Doppler velocimetry of the UtA obtained before delivery and postpartum. Left, right, and mean (m) peak systolic velocity (PSV), end-diastolic velocity (EDV), and pulsatility index (PI) were recorded. Our goal is to describe changes in these Doppler indices over time and to make comparisons with normal postpartum reference values.A total of 34 patients were included: 19 planned for uterine-sparing management and 15 planned for interval hysterectomy. No significant differences in mUtA PI, mPSV, and mEDV were documented between predelivery values and those obtained within the first eight weeks postpartum, however after 8 weeks there was a significant increase in mUtA PI (0.80–1.49; p < 0.001), while mUtA PSV (103.8–58.6 cm/s; p = 0.002) and mEDV (53.5–15.8 cm/s; p < 0.001) decreased significantly. Patients opting for uterine-sparing management who successfully retained their uterus showed a trend for higher mUtA PI, PSV, and EDV than those who underwent an interval hysterectomy. mUtA PI postpartum values were lower in our study group compared to those reported from postpartum patients without PAS.In comparison to patients without PAS, mUtA PI is markedly lower in LPIS patients in the first 8 weeks. In patients undergoing LPIS for PAS, UtA Doppler indices start to show significant changes at ≥ 8 weeks postpartum compared to predelivery values, with a significant increase in mUtA PI and a reduction in mUtA PSV and EDV. Future studies are needed to evaluate the clinical utility of these findings.
Keywords: color Doppler; conservative management; Doppler sonography; Doppler velocimetry; placenta accreta spectrum; placenta in situ; uterine artery; uterine preservation